Three essays on knowledge diffusion from academic-based research - Soares, Thiago José Cysneiros Cavalcanti (2019)
Universities around the world are increasingly engaging in activities of technology transfer, intensifying knowledge flows of academic-based research to firms. It is expected that these institutions play an active role in the development of the local economy. In fact, there was a sharp rise in patenting activities by universities over the last years. Moreover, universities have used different mechanisms to support university-industry technology transfer, as for example the implementation of regulatory frameworks and the creation of internal organizations aimed at facilitating interactions with firms. Although prior studies have comprehensively increased our understanding of the ways in which academic knowledge is disseminated, several important questions remain open. In this sense, the purpose of this dissertation is to investigate how university technologies are disseminated to firms, also examining the relationship between idiosyncratic attributes of universities, their regional context and university-industry technology transfer. The essays in this dissertation build on the knowledge spillover and technology transfer literatures, addressing different dimensions of the diffusion of academic knowledge. The dissertation consists of a general introduction, three essays, and a conclusion. The first essay relies on US patent databases, whereas the second and third use data in the context of Brazilian universities. Each essay, from a different perspective, explores dimensions that have not yet been addressed by prior literature. Investigating the dissemination patterns of technological knowledge embedded in university inventions is critical to understanding how and under circumstances scientific research disseminates and is deployed by firms. Along this line, this dissertation contributes to the field of innovation and technology management in several ways.